Effects of concussion on technical performance in professional Australian football - Clarke, A. C.; Middleton, K. J.; Gretgrix, H.; Pearce, A. J. (Science and Medicine in Football, 2023)
Introduction: There is limited research on the on-field performance of previously concussed athletes. The aim of this exploratory study was to investigate athlete technical performance pre- and post-concussion in Australian Football. Methods: Using publicly available data, male athletes who sustained a concussion during the 2016-19 professional Australian Football League seasons were analysed across five games pre- and post-concussion (concussion events n = 41, age 25.4 ± 3.5 years; control n = 39, age 25.2 ± 3.6 years). Mean technical performance metrics (goals, time-on-ground percentage, kicks, ground ball and disposal efficiency, contested marks) over the five games pre- and post-concussion, as well as within-athlete performance variability measures (standard deviation and coefficient of variation) were analysed. Results: Results showed no significant group-by-time interactions, nor effect of time (pre-post) for any technical performance metric. Similarly, the within-athlete standard deviation and coefficient of variation of technical performance metrics showed no group-by-time interaction, nor effect for time. Conclusion: This retrospective study has shown that athlete performance averaged over five games is not affected post-concussion in elite men`s Australian Football. Further prospective studies controlling for contextual match factors based on opposition and environmental conditions may be required to identify potential in-game technical performance changes following return-to-play from concussion.